Status of the Ban on Absentee Ownership of Farmland in Indonesia - Setiawan, Muhammad Rifaldi; S, Nathania Permata (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research investigates whether the ban on absentee land ownership retains its significance in today's context. The goal is to provide an updated perspective on the prohibition of absentee ownership of agricultural land in Indonesia. This investigation is normative, supported by empirical evidence, and employs both a statutory and a conceptual framework throughout the paper. The findings yield the following conclusions: initially, the underlying rationale for banning absentee land ownership is to ensure that agricultural land is actively cultivated and managed by its rightful owner for optimal yield. This emphasizes the principle that agricultural land should be actively utilized by its owner, as outlined in Article 10 of the UUPA. There is a necessity for oversight and preventive actions, such as rejecting registration applications, enforced by the district or city land office, to halt the ongoing issue of absentee land registration. Secondly, the importance of the absentee land ownership prohibition in Indonesia has diminished in light of contemporary realities, as the legislative framework established sixty years ago is no longer aligned with present-day societal conditions. The regulations regarding absentee land ownership require modernization; previously, ownership of agricultural land was restricted to the sub-district level, which should be revised or replaced by new laws allowing agricultural land ownership at the district or city level. This transformation would enable the new regulations to respond to the evolving landscape and address the increasingly complex challenges that arise.